Fenologia e polinizadores de Bertholletia excelsa Bonpl. introduzida em ambiente extra amazônico - Sousa, Clarissa de Moraes (2022)
The Brazil nut tree (Bertholletia excelsa Bonpl.) is native to the Amazon region, in hot and humid climates. Its main commercial product is the nut, which has great food importance due to its nutrient content, especially selenium. The exploitation of this non-timber forest product is mostly done in an extractive way, by collecting the fruits that have fallen on the forest floor. Its slaughter in Brazil is prohibited by federal law, due to its risk of extinction, being classified as vulnerable. One of the consequences of this legislation is the isolation of individuals, which affects their ecological relationships, causing their death. The pollination of the species is carried out by robust insects, as there is a need to lift the hood structure present in the flower to reach the nectary and, with that, carry out pollination; in addition, the dispersion is carried out by animals, which makes the species highly dependent on the fauna for its reproduction. There are few studies on the establishment of chestnut plantations outside the Amazon region, possibly because there are no reports of fruiting of the species on a larger scale outside its natural range, a fact that is occurring in an experimental plantation at the Federal University of Lavras. Thus, this study aimed to study the pollination and phenology of the species that is located in an ecotonal region between two world hotspots, the Cerrado and the Atlantic Forest. It is noted that the phenophases occur in a similar way to the region of origin, but at different rainfall conditions. As for pollination, a bee species was identified as a legitimate pollinator (Centris lutea) and some floral visitors, noting that there is effective pollination of flowers. Both the identification and the study of phenology constitute opportunities for the development of cultivation of the species outside its region of origin.